(untitled) (Medico Legal Update, 2020)
Assessment of Psychosocial Problems Among College Students in Selected educational institute, Kancheepuram District, Tamil Nadu. Aim of the study is to assess the prevalence of psychosocial problems among college students. Objectives of the study to assess the level of psychosocial problems among college students, to find out the association between the level of psychosocial problems with their selected demographic variables. Non experimental descriptive design used for this study. The samples were selected by using convenient sampling 120 college students from selected educational institution. Self structured demographic questionnaire used to assess the demographic variables and Standardised General Health Questionnaire (GHQ-28) used to assess the level of psychosocial problems in college students. Data collected from 01-04-2019 to 06-04-2019. The data collected from 120 college students (Girls and Boys) in the age group between 18 to 22 years in selected Educational institution. Dhanalakshmi Srinivasan Engineering College (Pooncheri), Tamil Nadu. The study result shows psychosocial problems among college students 8 (6.6%) have faced somatic symptoms, 62 (51.6%) anxiety/insomnia, 97 (80.83%) social dysfunction and 79 (65.83%) severe depression. Study shows that there was significant association between the level of psychosocial problems faced by college students with occupation status of parents, education status of parents, average family income and any history of mental illness (p value =<0.05).